Refinement of the Classroom Citizenship Behavior Scale. Issue 3 (27th May 2018) - Katt, James; Sivo, Stephen; Miller, Ann Neville; Brown, Tim; Scott, Andrea; Neel, Steve
Abstract : In its original presentation, scores on two of the three subscales of the Classroom Citizenship Behavior scale were highly reliable. Scores on the subscale measuring the third dimension of classroom citizenship behavior, Courtesy, had poor reliability. We inductively derived additional items for the Courtesy subscale and tested structure and reliability of the revised scale. Exploratory factor analysis indicated that the scale readily divided into three factors of six items each, consistent with the proposed model. Furthermore, the subscale scores associated with these factors demonstrated high reliability. Next, two additional communication classes completed the revised scale and confirmatory factor analyses were run on the new version of the three-factor scale. Fit indices were good. The revised Classroom Citizenship Behaviors scale provides a stronger tool for investigating student behaviors that contribute to the effective functioning of the classroom environment.